2015
DOI: 10.1186/s12974-015-0401-x
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced selective parvalbumin interneuron phenotype loss and cognitive impairments may be mediated by NADPH oxidase 2 activation in mice

Abstract: BackgroundSepsis-associated encephalopathy (SAE) is a diffuse brain dysfunction caused by many pathological events, including neuroinflammation and oxidative stress damage. Increasing evidence suggests that parvalbumin (PV) interneurons play a key role in the cognitive process, whereas the dysfunction of these interneurons has been implicated in a number of major psychiatric disorders. Here, we aimed to investigate whether enhanced inflammation and oxidative stress-mediated PV interneuron phenotype loss plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 31 publications
(40 reference statements)
2
50
0
Order By: Relevance
“…Compared to the widely used lipopolysaccharide model, the CLP model is clinically relevant because it has a feature shared with human sepsis-induced cognitive impairment (4,13,14). Although many mechanisms, including oxidative stress, endothelial dysfunction, inflammation, unbalanced neurotransmission, mitochondrial dysfunction, and cell death have been implicated in the pathogenesis of sepsis-associated cognitive impairment (16)(17)(18)(19)(20), the precise mechanism remains to be elucidated. In this study, we showed that β2-microglobulin deficiency protected mice from sepsis-induced neurobehavioral and biochemical abnormities, suggesting β2-microglobulin may serve as a therapeutical target for sepsis-associated cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the widely used lipopolysaccharide model, the CLP model is clinically relevant because it has a feature shared with human sepsis-induced cognitive impairment (4,13,14). Although many mechanisms, including oxidative stress, endothelial dysfunction, inflammation, unbalanced neurotransmission, mitochondrial dysfunction, and cell death have been implicated in the pathogenesis of sepsis-associated cognitive impairment (16)(17)(18)(19)(20), the precise mechanism remains to be elucidated. In this study, we showed that β2-microglobulin deficiency protected mice from sepsis-induced neurobehavioral and biochemical abnormities, suggesting β2-microglobulin may serve as a therapeutical target for sepsis-associated cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This has been recently summarized as the 'interneuron energy hypothesis' [15]. Although the causes of PV interneuron loss in PTSD are not yet understood, PV interneurons are thought to be vulnerable to oxidative stress [32]. Accumulating evidence has suggested that various subunits of NADPH oxidase in the plasma membrane are highly expressed in cortical neurons and can also generate ROS [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are widely discussed cytokines such as interleukins (interleukin-1, -6, -10) [37,64], tumor necrosis factor (TNF)-alpha [65,66], complement C5a [67], and cascade [68].…”
Section: Effect Of Cytokine Storm On Brain Functionmentioning
confidence: 99%